Apolipoprotein E Polymorphism and Carotid Intima Medial Thickness Progression in Post Ischemic Stroke Patient: Apolipoprotein E Polymorphism and Carotid Intima Medial Thickness Progression in Post Ischemic Stroke Patient - Kurnianto, Aditya; Retnaningsih, Retnaningsih; Tugasworo, Dodik; Andhitara, Yovita; Ardhini, Rahmi; Budiman, Jethro (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Background : Apolipoprotein E (APOE) gene is believed to associate with cholesterol level, a risk factor of ischemic stroke. CIMT (carotid intima-media thickness) can be used to determine the degree of atherosclerosis. Increased CIMT may predict ischemic stroke recurrence. This study aimed to determine association between increased CIMT in post ischemic stroke patients and APOE genotype. Methods : This was an epidemiological prospective study involving 71 post ischemic stroke patients (1 month from onset), admitted from 2012 to 2013. CIMT was examined with carotid duplex ultrasound at 1st, 6th, and 12nd month after stroke onset. APOE gene polymorphism was examined using HRM (high-resolution melting) which is a simple method, accurate, and sensitive for genotyping. Results : We found 5 APOE gene variation categories, i.e. E2E3, E2E4, E3E3, E3E4, and E4E4. The most common allele was E3 and genotype groups E3E3 was the majority of the population. E2E4 allele had the highest CIMT level among others, in the 1st month, 6th month, and 12nd month after stroke, with no association with hypertension, diabetes, and hypercholesterolemia. E3E3 allele was most often associated with hypertension, diabetes mellitus, dyslipidemia, and hyperhomocysteinemia. Conclusion : The results showed that APOE genotype E2E4 may independently constitute risk factor for atherosclerosis progression (CIMT) in post ischemic stroke patients. While the E3E3 genotype was often associated with hypertension, diabetes mellitus, dyslipidemia, and hyperhomocysteinemia. Our results suggest that APOE E4 was not an important risk factor for carotid atherosclerosis in post ischemic stroke patient.